Analisis Jenjang Metakognisi Menurut Swartz dan Perkins pada Mahasiswa dalam Penyelesaian Masalah Statistika (Studi pada Mahasiswa Semester IV Prodi PKAUD FIPK IAKN Ambon) : Penelitian - Wilhelmus Labobar; Vabio Lekahena; Naema Molly (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to analyze the levels of metacognition based on the framework of Swartz and Perkins (as developed by Laurens) and the statistical problem-solving abilities of fourth-semester students in the Early Childhood Education Program at FIPK IAKN Ambon. It employs a descriptive approach with both quantitative and qualitative data. The results show: (1) Metacognitive levels: (a) High scorers fall under Reflective and Semi-Reflective Use, demonstrating deep understanding and solution evaluation; (b) Medium scorers fall under Strategic and Semi-Strategic Use, capable of planning strategies but lacking in evaluation; (c) Low scorers fall under Tacit and Aware Use, only grasping basic problems. (2) Problem-solving performance: (a) Students at the Strategic Use level meet metacognitive indicators but only on certain questions; (b) Semi-Reflective Use students solve problems thoroughly and understand concepts; (c) Semi-Strategic Use students complete only part of the tasks; (d) Aware Use students struggle to understand the questions; (e) Tacit Use students tend to answer randomly.